PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MELAKUKAN AKTIVITAS MERGER DAN AKUISISI - Octaviani, Maeninta (Buletin Ekonomi, 2018)
This study aims to determine the impact of conducting merger and acquisition activities on company performance. In this study using the company's financial statements of the period 2012-2016 at the company in Indonesia Stock Exchange (BEI) which conduct merger and acquisition activities in 2014. The population in this study includes all public companies listed on the Indonesia Stock Exchange (BEI). The sample is determined using purposive sampling technique. And based on source obtained 5 companies doing merger and acquisition activity. This type of research is a kind of comparative quantitative research. The method of analysis of data that dogunakan is paired t-test Normality test conducted to determine the data used normal distribution or not. The result of paired sample t-test for the liquidity ratio projected by current ratio (CR), the ratio of activity proxy to fixed assets turnover (FAT) and total asset turnover (TAT), solvency ratios projected with debt to total assets ratio (DTAR), profitability ratio projected with net profit margin (NPM) and return on assets (ROA) at 1 and 2 years after mergers and acquisitions have a value of Aymp.Sig (2-tailed) greater than the specified significance value = 0,01 (> 0,01). This can be interpreted that there is no significant difference in current ratio, fixed asset turnover, total asset turnover, debt to total assets ratio, net profit margin and return on assets after merger and acquisition.Keywords: Financial perfomance, merger, and acquisition.